The Relationship of Residential Density and Smoking Habits with The Incidence of Acute Respiratory Infections (Ari) In Toddlers in The Working Area at The Sausu Public Health Clinic, Parigi Moutong District, Central Sulawesi Province - Hasanudin; Novarianti; Saharudin; Maryam (Kirana Publisher (KNPub), 2024)
ISPA is a respiratory tract disease that can cause mild to fatal infections due to environmental factors. ISPA in toddlers is caused by several factors including environmental factors, namely type of house, ventilation, type of floor, lighting, residential density, humidity, type of fuel and smoking habits. The aim of this research is to find out whether there is a relationship between population density and smoking habits with the incidence of ISPA in toddlers in the Sausu Community Health Center Working Area, Parigi Moutong Regency, Central Sulawesi Province. Analytical with the aim of finding relationships between one variable and other variables. The population was 167 samples, 62 toddlers suffering from ISPA and not suffering from ISPA. There is no relationship between the density of house occupants and the incidence of ISPA with a P-Value ≥ 0.252 > 0.05, so Ho is accepted and Ha is rejected. There is no relationship between home smoking habits and the incidence of ARI with a P-Value ≥ 1,000 > 0.05, so Ho is accepted and Ha is rejected. Keep the home environment clean and do not smoke near children, inside the house. Because it will have an impact on the health of the toddler and the entire family.